The Use of Audio Visual Media to Improve Motivation and Locomotor Learning Outcomes - Akhifah, Hasna; Putri, Wulandari; Nugroho, Wildan; Yudha, Robby (TEGAR: Journal of Teaching Physical Education in Elementary School, 2024)
This study aims to improve motivation and locomotor learning outcomes by using audio-visual media as a learning medium. This study was motivated because in the learning process, especially in locomotor learning, teachers still use conventional methods, teachers are also still lacking in the use of media during learning and teachers still have difficulty in fostering motivation and improving locomotor learning outcomes in students. The use of audio-visual media is expected to help overcome problems in the learning process. The method used in this study is Classroom Action Research (CAR), in this study two cycles were carried out, there were four meetings. This research was carried out through four stages, namely planning, implementation, observation and reflection. The participants used in this study were all students of class IC SDN Cisintok totaling 23 students, consisting of 12 female students and 11 male students. The sample used was the total sampling technique. The instruments used in this study were Questionnaires or questionnaires and Locomotor Tests. The results of this study indicate that student motivation has received an average of 91.60 which means there is an increase in motivation from the use of audio-visual media. With a percentage of 30% high and 70% very high. Likewise, the results of locomotor learning have increased by using audio-visual media and get an average of 85.78. With a percentage of 100% very good. So, it can be concluded that there is an increase in motivation and locomotor learning results by using audio-visual media.